An in-depth analysis of the variable cyclotron lines in GX 301-2 - Zalot, Nicolas; Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Ballhausen, Ralf; Zainab, Aafia; Pottschmidt, Katja; Fürst, Felix; Thalhammer, Philipp; Islam, Nazma; Diez, Camille M.; Kretschmar, Peter; Berger, Katrin; et al. (Astronomy & Astrophysics, 2024)
Context. The high-mass X-ray binary system GX 301-2 is a persistent source with a well-known variable cyclotron line centered at 35 keV. Recently, a second cyclotron line at 50 keV has been reported with a presumably different behavior than the 35 keV line. Aims. We investigate the presence of the newly discovered cyclotron line in the phase-averaged and phase-resolved spectra at higher luminosities than before. We further aim to determine the pulse-phase variability of both lines. Methods. We analyze a NuSTAR observation of GX 301-2 covering the pre-periastron flare, where the source luminosity reached its peak of ∼4× 1037 erga s-1 in the 5 -50 keV range. We analyze the phase-averaged spectra in the NuSTAR energy range from 3.5- 79 keV for both the complete observation and three time segments of it. We further analyze the phase-resolved spectra and the pulse-phase variability of continuum and cyclotron line parameters. Results. We confirm that the description of the phase-averaged spectrum requires a second absorption feature at 51.5-1.0+1.1 keV besides the established line at 35 keV. The statistical significance of this feature in the phase-averaged spectrum is > 99.999%. We further find that the 50 keV cyclotron line is present in three out of the eight phase bins. Conclusions. Based on the results of our analysis, we confirm that the detected absorption feature is very likely to be a cyclotron line. We discuss a variety of physical scenarios that could explain the proposed anharmonicity, but also outline circumstances under which the lines are harmonically related. We further present the cyclotron line history of GX 301-2 and evaluate concordance among each other. We also discuss an alternative spectral model including cyclotron line emission wings.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Stars: magnetic field; Stars: neutron; X-rays: binaries